Scribal Assimilation as Inter-Textual Allusion - Lyons Michael A. (Perichoresis: The Theological Journal of Emanuel University)
In this essay I examine instances of scribal assimilation in ancient Jewish scripture and identify the literary features that triggered scribal recollections of other texts. I argue that some instances of assimilation can be understood as inter-textual allusion, and should be analyzed as such with reference to their formal features and possible exegetical functions. Finally, I conclude with reflections on the relationship between assimilation and the formation of a scripture collection.